Editorial - Mani Man Singh Rajbhandari (Journal of Interdisciplinary Sciences)
Dear Readers, We are pleased to announce the publication of Volume 4, Issue 1 2020. This issue covers manuscripts from different discipline to incorporate interdisciplinary sciences into one platform. Published in this issue, research papers related to economic, sciences, education, social and outdoor/sports leadership are published. Our next issue will be published in November 2020 and we invite authors, researchers, managers, leaders, scientists, students and others for paper submission. The Journal of Interdisciplinary Sciences is an open access, which offers free submissions, free publication and free open access to download its published research paper from the journal’s website http://journalofinterdisciplinarysciences.com/. Globally we all are facing the painstaking challenges to overcome this COVID-19 Novel Coronavirus Pandemic, this is the time to remain strong and overcome this pandemic with peace, calm and inner strength. Remain Safe and keep well. Let us join and collaborate together to ENRICH the BEAUTIFUL MINDS TOWARDS INTELLIGENT MINDS Mani Man Singh Rajbhandari. Ph.D. Founder and Editor-in-Chief Journal of Interdisciplinary Sciences (JIS) www.journalofinterdisciplinarysciences.com